Application of pediatric massage combined with Traditional Chinese Medicine application in antipyretic treatment of children with exogenous fever (小儿推拿联合中药敷贴在外感发热患儿退热中的应用) - TANG Xianlan (汤先兰); GAN Na (甘娜); HUANG Biqiu (黄碧秋) (中西医结合护理)
Objective To explore the feasibility of pediatric massage combined with Traditional Chinese Medicine application in the antipyretic treatment of children with exogenous fever. Methods Totally120 children with exogenous fever admitted to the hospital from July 2020 to June 2022 were included as study objects , and 60 of them were divided into control group based on the single-day and double-day admission sequencing method, and were treated with conventional western medicine antipyretic regimen; Another 60 cases were enrolled in the treatment group, and treated with massage combined with Traditional Chinese Medicine application. The curative effect, axillary temperature and antipyretic time between the two groups after systematic treatment were compared. Results The excellent and good rate of treatment in the treatment group (98. 33%) was higher than that in the control group (81. 67%), with a significant difference(P＜0. 01). The axillary temperature level of the treatment group at 6~12h, 24h, 36h and 48h after medication was lower than that of the control group, respectively(P＜0. 01). No adverse reaction was reported in the treatment group; There were 3 cased of headache and 7 cases of nausea/vomiting reported in the control group. The antipyretic onset time and complete antipyretic time in the treatment group were shorter than those in the control group (P＜0. 01). Conclusion In the antipyretic treatment of children with exogenous fever, the combination of massage and Traditional Chinese Medicine application is safe and effective to further improve the antipyretic effect of children. (目的 探讨在外感发热患儿退热治疗中运用推拿联合中药敷贴治疗的可行性。方法 选取2020年7月—2022年6月医院收治的外感发热患儿120例为研究对象, 基于单双日入院排序法作为分组依据, 其中60例纳入对照组, 给予常规西药退热方案对症治疗; 另外60例纳入治疗组, 采用推拿联合中药敷贴治法治疗。评价两组疗效, 记录和对比腋温、退热时间等指标差异。结果 治疗组治疗优良率(98. 33%)高于对照组(81. 67%), 差异有统计学意义(P＜0. 01)。用药后6～12 h、24 h、36 h、48 h治疗组腋温水平均低于对照组, 差异有统计学意义(P＜0. 01)。治疗组无不良反应发生; 对照组发生头痛3例, 恶心呕吐7例。治疗组退热起效时间和完全退热时间短于对照组, 差异有统计学意义(P＜0. 01)。结论 在外感发热患儿的退热治疗中, 采用推拿联合中药敷贴治法能够进一步提升退热效果, 治疗安全性方面较之西药更佳, 整体疗效显著。)